An Upper Bound for the Tensor Rank. (23rd May 2013) - Ballico, E.
Abstract : Let T be a tensor of format m 1 + 1 × ⋯ × m s + 1, m 1 ≥ ⋯ ≥ m s > 0, over ℂ . We prove that T has tensor rank at most ∏ i ≠ 2 m i + 1 .